A New Protocol to Evaluate the Effect of Topical Anesthesia - List, Thomas (Anesth Prog, 2014)
This double-blind, placebo-controlled, randomized cross-over clinical experimental study tested the reliability, validity, and sensitivity to change of punctuate pain thresholds and self-reported pain on needle penetration. Female subjects without orofacial pain were tested in 2 sessions at 1- to 2-week intervals. The test site was the mucobuccal fold adjacent to the first upper right premolar. Active lidocaine hydrochloride 2% (Dynexan) or placebo gel was applied for 5 minutes, and sensory testing was performed before and after application. The standardized quantitative sensory test protocol included mechanical pain threshold (MPT), pressure pain threshold (PPT), mechanical pain sensitivity (MPS), and needle penetration sensitivity (NPS) assessments. Twenty-nine subjects, mean (SD) age 29.0 (10.2) years, completed the study. Test-retest reliability intraclass correlation coefficient at 10-minute intervals between examinations was MPT 0.69, PPT 0.79, MPS 0.72, and NPS 0.86. A high correlation was found between NPS and MPS (r = 0.84; P < .001), whereas NPS and PPT were not significantly correlated. The study found good to excellent test-retest reliability for all measures. None of the sensory measures detected changes in sensitivity following lidocaine 2% or placebo gel. Electronic von Frey assessments of MPT/MPS on oral mucosa have good validity.